Autophagy regulates spermatid differentiation via degradation of PDLIM1. Issue 9 (1st September 2016) - Shang, Yongliang; Wang, Hongna; Jia, Pengfei; Zhao, Haichao; Liu, Chao; Liu, Weixiao; Song, Zhenhua; Xu, Zhiliang; Yang, Lin; Wang, Yanfang; Li, Wei
ABSTRACT: Spermiogenesis is a complex and highly ordered spermatid differentiation process that requires reorganization of cellular structures. We have previously found that Atg7 is required for acrosome biogenesis. Here, we show that autophagy regulates the round and elongating spermatids. Specifically, we found that Atg7 is required for spermatozoa flagella biogenesis and cytoplasm removal during spermiogenesis. Spermatozoa motility of atg7 -null mice dropped significantly with some extra-cytoplasm retained on the mature sperm head. These defects are associated with an impairment of the cytoskeleton organization. Functional screening revealed that the negative cytoskeleton organization regulator, PDLIM1 (PDZ and LIM domain 1 [elfin]), needs to be degraded by the autophagy-lysosome-dependent pathway to facilitate the proper organization of the cytoskeleton. Our results thus provide a novel mechanism showing that autophagy regulates cytoskeleton organization mainly via degradation of PDLIM1 to facilitate the differentiation of spermatids.